Question

# {y= -2x-1 y=3x-4y=-51

Answer

Class, we have been given a system of equations y = -2x - 1 and y = 3x - 4. The solution to this system is (0.6, -2.2). Now, let's work out how to solve this system of equations. We begin by substituting y = 3x - 4 in the first equation y = -2x - 1. This gives us 3x - 4 = -2x - 1. We then collect like terms and simplify the equation to get 5x = 3. After dividing both sides by 3, we get x = 0.6. Substituting x = 0.6 into y = 3x - 4, we obtain y = -2.2. Thus, the solution to the system of equations is (0.6, -2.2). For further information on how to solve a system of equations, please check out brainly.com/question/13729904 #SPJ1.